2012
DOI: 10.1007/s00221-012-3169-6
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the interaction between pathological upper limb synergies and compensatory trunk movements during reach-to-grasp after stroke: a cross-sectional study

Abstract: The aim of the present study was to identify how pathological limb synergies between shoulder and elbow movements interact with compensatory trunk movements during a functional movement with the paretic upper limb after stroke. 3D kinematic joint and trunk angles were measured during a reach-to-grasp movement in 46 patients with stroke and 12 healthy individuals. We used principal component analyses (PCA) to identify components representing linear relations between the degrees of freedom of the upper limb and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 33 publications
7
49
0
4
Order By: Relevance
“…1e). During the reaching motions, three types of compensatory synergies were commonly elicited, including an excessive axial trunk rotation (TR), trunk lean-forward (TLF) [33,34] and shoulder elevation movements (SE) [13,15]. Each subject performed the three types of reaching tasks with his/her affected side and healthy side.…”
Section: Experimental Setup and Instrumentsmentioning
confidence: 99%
“…1e). During the reaching motions, three types of compensatory synergies were commonly elicited, including an excessive axial trunk rotation (TR), trunk lean-forward (TLF) [33,34] and shoulder elevation movements (SE) [13,15]. Each subject performed the three types of reaching tasks with his/her affected side and healthy side.…”
Section: Experimental Setup and Instrumentsmentioning
confidence: 99%
“…Numerous studies have demonstrated that stroke patients exhibit excessive trunk movements during pointing and reaching, [6][7][8][9][10][11][12][13] a compensatory motor strategy to extend arm reach when shoulder and elbow movement and control is impaired. 14,15 Excessive use of compensatory movements can result in secondary complications such as muscle contractures, joint misalignment, pain, limb disuse, and increased energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…сенного церебрального инсульта представляет определенные трудности, и работы такого содержания в литературе встречаются относительно редко [16]. Необходимость в арсенале врача средств объективного анализа для больных, перенесших церебральный инсульт, весьма актуальна [17]. В последние годы такими средствами часто становятся инерционные сенсоры [17,18].…”
Section: Introductionunclassified
“…Необходимость в арсенале врача средств объективного анализа для больных, перенесших церебральный инсульт, весьма актуальна [17]. В последние годы такими средствами часто становятся инерционные сенсоры [17,18].…”
Section: Introductionunclassified